America's doll house the miniature world of Faith Bradford - Bird, William L.; Bradford, Faith, 1880-1970.; ebrary, Inc. (Washington, D.C. : Smithsonian Institution, National Museum of American History ; New York : In association with Princeton Architectural Press, 2010)
"One of the most popular exhibits at the Smithsonian Institute is a dollhouse. Sitting on the museum's third floor is the five-story home donated to the museum by Faith Bradford, a Washington, D.C., librarian, who spent more than a half-century accumulating and constructing the 1,354 miniatures that fill its 23 intricately detailed rooms. When Bradford donated them to the museum in 1951, she wrote a lengthy manuscript describing the lives of its residents: Mr. and Mrs. Peter Doll and their ten children, two visiting grandparents, twenty pets, and household staff. Bradford cataloged the Dolls' tastes, habits, and preferences in neatly typed household inventories, which she then bound, along with photographs and fabric samples, in a scrapbook" --
The miniature world of Faith Bradford : an illustrated history -- The dolls' house : room by room -- The scrapbook : fabric swatches of house furnishings.
Includes bibliographical references.
Electronic reproduction.
Keywords: Bradford, Faith, -- 1880-1970 -- Art collections; National Museum of American History (U.S.); Dollhouses -- United States; Electronic books